Performance information system and student governance Politeknik Negeri Medan - Kholil, Ahmad; Hutagalung, Gabriel Ardi; Zuardi, Muhammad (Jurnal Mandiri IT, 2025)
Structured and effective student governance is one of the keys to success in creating a dynamic and productive academic environment at the Politeknik Negeri Medan. In an effort to increase transparency and efficiency in the management of student activities, especially related to activities, competitions and scholarships, it is necessary to implement an integrated Student Performance and Governance Information System. This system will cover various student activities, from organizations, social activities, to self-development, as well as three main competition categories: Sports and Arts Competitions, and Academic Competency Competitions. Scholarship management is also the main focus to provide financial support to students who excel or need assistance. With this integration, Politeknik Negeri Medan can improve data management efficiency, strengthen supervision, and provide easier and faster access to all parties involved, thereby creating a learning environment that is more structured and oriented towards achieving academic and non-academic achievements.